The slow uptake of PMP in South Africa described and explained using grounded theory methods - Maape, Neto (Department of Information Systems, 2025)
Purpose – “Quo vadis TAM?” was a question asked by Benbasat and Barki in an inspired 2007 critique of the intense focus of the Technology Adoption Model (TAM) in Information Systems (IS), referring to its discovery as a blessing but its overuse as a curse that has resulted in TAM being unassailable. A response by Straub and Burton-Jones in 2007 partially titled “Veni, Vidi, Vici” agreed with most of these assertions, but felt that characterising TAM as unassailable requires inquiry to assess if aspects of TAM are methodological artifacts. This research aimed to act on these two inspired studies. This study did so by developing an explanation of the slow uptake of Proximity Mobile Payment (PMP) in two South African urban areas using Grounded Theory Methods (GTM). The theory developed was grounded in the data collected and was unconstrained by limits of most PMP studies in three ways: it does not use any established adoption theories, it makes use of an interpretivist paradigm unlike most PMP studies, and it focused on both adopters and non-adopters. South Africa is unique to other developing countries as it has a relatively high number of banked individuals who own a smart phone. However, South Africans are slow to take up the use of PMP. This makes it perfect for a study which seeks to describe the sentiments they hold regarding PMP to explain why so few of them have decided to take up PMP. Design/methodology/approach – This study sought to describe sentiments of participants related to PMP to aid the development of a theory that helps explain its slow uptake. An interpretivist stance with constructivist philosophical assumptions was used in this research. The study made use of semi-structed qualitative interviews to collect data, which was analysed using constructivist GTM. Findings – The study answers Straub and Burton-Jones questioning if that the main constructs of TAM are methodological artifacts or inherent to technology adoption, by confirming the latter as they were part of the constructs revealed in analysis that was grounded in the data. However, other constructs were revealed which may be contextual to South Africa, confirming Benbasat and Barki's assertion that TAM's narrow approach may miss other more contextual factors. The slow uptake of PMP in South Africa can be explained by considering constructs of TAM along with four others revealed in this study. Other findings are that QR scanning may be obsolete in PMP offerings, PMP non-adopters in South Africa are price sensitive and along with crime rates, these may be key factors inhibiting PMP adoption regardless of perceived usefulness and ease of use. Research limitations– The research was understandably limited by the time constraints of a master's programme and it being cross sectional. Contributions to literature – The study contributes to literature by revealing potential future studies on best practice approaches to inquiry into both adopters and non-adopters, technology changes in the PMP market and contextual factors unique to South Africa which may influence PMP adoption.